The construct validity of pre-built Likert-type attitude scales - Couper, Michael Patrick (Department of Sociology, 2015)
A number of survey research efforts in South Africa have neglected to examine the validity of attitude scales designed for and validated on other populations. Methods for testing the validity of attitude scales constructed using Likert' s ( 1932) sum mated ratings method are discussed and demonstrated using Dean's (1961) Social Alienation Scale as an example. The use of factor analysis and cluster analysis in the construct validation of such a scale is examined. The results not only raise doubts about the validity of this particular scale when applied to a non-representative sample of 404 so-called Coloured and White respondents in Cape Town, but also indicate that extreme caution should be exercised when applying such an attitude scale in a population other than that for which it was originally designed and tested.